Hierarchical Multi-Blockchain System for Parallel Computation in Cryptocurrency Transfers and Smart Contracts - Nam-Yong Lee (Applied Sciences, 2021)
Most of the existing smart-contract-based cryptocurrencies, such as Ethereum, use an account-based ledger. However, while the account-based model is advantageous for the efficient use of smart contracts and the increased exchangeability of cryptocurrencies, it is not well-suited to the parallel execution of smart contracts. However, unspent transaction output (UTXO)-based cryptocurrencies such as Bitcoin are advantageous for parallel cryptocurrency transfers but not well-suited to smart contracts. In this paper, we propose a hierarchical multi-blockchain system that uses multiple pairs of sidechain and dual-sidechains extended by independent block mining in their blockchain networks and a mainchain to control the branching and connection process of sidechains and dual sidechains. In the proposed method, one pair of a sidechain and dual sidechain forms one shard. The proposed method uses multiple shards to execute cryptocurrency transfers and smart contracts in parallel. In addition, the proposed model uses an accoutchain to record the resulting state changes generated by smart contract executions in each shard and securely share them with all other nodes. The proposed method uses a modifiable blockchain structure for the accountchain to obtain the database to record the smart contract execution results in each shard in as small and secure a manner as possible to ensure that all nodes trust the recorded results without executing smart contracts themselves. To examine the validity of the proposed method, we conducted a threat analysis of the proposed method by examining possible attacks in various scenarios as a thought experiment. This threat analysis concludes that the proposed blockchain system can execute smart contracts in parallel while keeping the concurrency in resulting state changes secure.